Analisis Kualitas Pelayanan PT Kereta Api Divre Ii Sumbar Rute Padang – Pariaman - Fajri Aulia Hakim; Armida Armida (Universitas Negeri Padang, 2022)
This study aims to analyze the effect of service quality on community satisfaction of users of the West Sumatra Divre 2 Railroad service on the Padang - Pariaman route. Can be seen from the 5 service quality indicators, namely 1) tangible 2) reliability 3) responsive 4) assurance 5) Empathy. This type of research is a descriptive study using a quantitative approach that uses primary data as research data and was obtained from a questionnaire filled out by the community users of the West Sumatra Divre 2 Railroad service, specifically the Padang - Pariaman route. The sample of this research is 100 people or users of the Railroad service. The sampling technique used is probability sampling using accidental sampling method. The data analysis technique used is descriptive analysis and GAP analysis (gap or difference between perception and expectations) using Cartesian diagrams. The results of the analysis show that the five indicators of service quality in PT KeretaApiDivre 2 West Sumatra - Padang route Pariaman are in both categories in terms of perception and expectations of service users. Providers of the results of the analysis with the importance of matrix performance and Cartesian diagrams of all indicators in the table of recipient or service user satisfaction index. The results showed that the quality of service at PT KeretaApiDivre 2 West Sumatra route Padang - Pariaman has provided good service to the people who use Railroad services. Therefore, it is suggested to PT KeretaApi to continue to improve the quality of service to the community of Train users.